Applying Value Engineering Technique to Health Clinics During The Design Stage (Salah Al Din Governorate A Case Study) - Shareef, Noran; Ibrahim, Abdul Rahman (Iraqi Journal of Civil Engineering, 2022)
Because of rising the need for health clinics in recent years, as well as the current economic climate, the researcher used value engineering to reduce costs while retaining the necessity of these initiatives. The aim of this study is to increase the value of health clinics through applying value engineering approach to the main building (two and a half floors). Collected data, function analysis, brainstorming and alternatives, evaluating and selection, and generating the value report are the steps followed. According to the study, using the value engineering process resulted in a cost savings of 32.15 percent, or (258.305.000) million Iraqi dinars without jeopardizing the desired outcome.